Improving Efficiency of Aluminium Sacrificial Anode Using Cold Work Process - Asmara, Y. P.; J. P., Siregar; Cionita, Tezara; Chang, Tai Ann (IOP Publishing, 2016)
Aluminium is one of the preferred materials to be used as sacrificial anode for carbon steel protection. The efficiency of these can be low due to the formation of oxide layer which passivate the anodes. Currently, to improve its efficiency, there are efforts using a new technique called surface modifications. The objective of this research is to study corrosion mechanism of aluminium sacrificial anode which has been processed by cold work. The cold works are applied by reducing the thickness of aluminium sacrificial anodes at 20% and 40% of thickness reduction. The cathodic protection experiments were performed by immersion of aluminium connected to carbon steel cylinder in 3% NaCl solutions. Visual inspections using SEM had been conducted during the experiments and corrosion rate data were taken in every week for 8 weeks of immersion time. Corrosion rate data were measured using weight loss and linear polarization technique (LPR). From the results, it is observed that cold worked aluminium sacrificial anode have a better corrosion performance. It shows higher corrosion rate and lower corrosion potential. The anodes also provided a long functional for sacrificial anode before it stop working. From SEM investigation, it is shown that cold works have changed the microstructure of anodes which is suspected in increasing corrosion rate and cause de-passivate of the surface anodes.